A bivalent fusion vaccine composed of recombinant Apx proteins shows strong protection against Actinobacillus pleuroneumoniae serovar 1 and 2 in a mouse model. Issue 2 (2nd April 2019) - Park, Byung-Sun; Lee, Nakhyung
ABSTRACT: Actinobacillus pleuropneumonia (APP) causes porcine pleuropneumoniae, resulting in severe economic losses in the swine industry. Since there are diverse serotypes of APP, it is necessary for vaccines to induce cross-protection. In this report, we developed a bivalent fusion vaccine, the L vaccine composed of ApxIA and ApxIIA fragments. According to the experimental results of the L vaccine, recombinant protein specific-IgG antibody level increased significantly as well as Apx toxin specific-IgG antibody, suggesting toxin-neutralizing effect. Also, the production of both IgG1 and IgG2a indicates this fusion vaccine induces Th1 and Th2 immune reactions. In addition, lymphocytes were proliferated and immune related-cytokines of TNF-α, IL-12, IFN-γ and IL-5 were detected in the serum after the vaccination. The L vaccine showed a perfect cross-protection against APP serovar 1 and 2 that each secrete different Apx exotoxins. These findings reveal that the fusion L vaccine induces specific humoral and cellular immunity, leading to a perfect cross-protection against A. pleuropneumoniae infections in a murine model. Abstract : Fusion vaccine L, Apx toxoid vaccine, induces protection against both Actinobacillus pleuropneumoniae serovar 1 and 2.